Effectiveness Of Treatment of Dysbiosis of the Artificial Vagina After Sigmoidal Colpopoesis in Dynamics - Zarif Shamsiddinovich, Ahmedov; Bahodur Boltaevich, Negmadjanov (Journal of Neonatal Surgery, 2025)
Dysbiosis of the artificial vagina after sigmoidal colpopoesis is a complex and understudied issue in gynecological practice. This study evaluates the effectiveness of various treatments for dysbiosis in patients who have undergone sigmoidal colpopoesis. The study aims to identify the most effective therapeutic strategies, focusing on bacterial composition, prevention of infection, and recovery of the vaginal microflora in the post-operative period. The results suggest that a combined approach, including antibiotic therapy and probiotics, shows the highest effectiveness in restoring the natural balance of microflora and improving the patients' quality of life. The study emphasizes the importance of personalized treatment plans based on individual patient conditions and microbial profiles.